2023
DOI: 10.1002/cam4.5550
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA DICER1‐AS1 promotes colorectal cancer progression by activating the MAPK/ERK signaling pathway through sponging miR‐650

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
(82 reference statements)
0
5
0
Order By: Relevance
“…The best-known examples of MAPK/ERK-pathway overactivity come from various cancers in which the activity has been linked to cell proliferation, dedifferentiation, and a lack of apoptosis [ 59 ]. Furthermore, several studies have found that ERK activation in tumor cells leads to enhanced migration capability that can be alleviated by specific MAPK/ERK pathway inhibitors [ 60 62 ]. Thus, activated MAPK/ERK signaling could partly contribute to the enhanced mobility of ddR1 + R2 cells inside 3D Matrigel.…”
Section: Discussionmentioning
confidence: 99%
“…The best-known examples of MAPK/ERK-pathway overactivity come from various cancers in which the activity has been linked to cell proliferation, dedifferentiation, and a lack of apoptosis [ 59 ]. Furthermore, several studies have found that ERK activation in tumor cells leads to enhanced migration capability that can be alleviated by specific MAPK/ERK pathway inhibitors [ 60 62 ]. Thus, activated MAPK/ERK signaling could partly contribute to the enhanced mobility of ddR1 + R2 cells inside 3D Matrigel.…”
Section: Discussionmentioning
confidence: 99%
“…The MAPK signalling pathway can transduce extracellular signals into the nucleus and has been reported to regulate the proliferation, apoptosis, migration, invasion, and chemoresistance of colon cancer cells [25][26][27][28]. The RAF/MEK/ERK signal transduction cascade is a classical MAPK pathway that can regulate cell proliferation, motility, and survival in various pathological and physiological processes.…”
Section: Discussionmentioning
confidence: 99%
“…The DANCR/miR-185-5p/HMGA2 axis is involved in the migration and invasion processes of CRC ( 92 ). The upregulation of DICER1-AS1 promotes CRC migration and invasion by activating the MAPK/ERK signaling pathway through a sponge-like effect on miR-650 ( 93 ). Bin et al.…”
Section: Lncrnas Regulate Invasion and Metastasismentioning
confidence: 99%